Die Jagd als Leidenschaft in den Briefen und Schriften Maximilians I. - Raphael Einetter (Historia.scribere)
The following paper deals with the significance of hunting in the life of emperor Maximilian I (1459 – 1519) in relation to his publications and letters. It will examine Maximilian’s enthusiasm for hunting and take his idealized self-expression in writings like Weißkunig or Theuerdank into account. Furthermore, this treatise will discuss his correspondence, in which hunting is referred to frequently.